A rainfall-based flash flood warning method integrating spatial stratification and multi-mode discrimination - Liu, Xiangning; Dou, Yanhong; Liu, Tianyu; Xie, Min (Frontiers in Earth Science, 2026)
Rainfall -based methods are widely used for flash flood monitoring and warning. However, the conventional approach of issuing an alert based on any single associated station exceeding a threshold leads to frequent false alarms, hindering timely evacuations. This study proposes a method integrating spatial stratification and multi-mode discrimination. The method innovatively classifies rainfall stations associated with each village according to the spatial relationships among station–village, station–watershed, and station–station pairs. A multi-mode warning framework combining single-station, multi-station, and areal rainfall warnings is developed, with the appropriate warning mode determined by the station–village distance and the upstream watershed area of the village. Validation was conducted in six representative villages across Fujian Province. These villages were selected to encompass diverse watershed characteristics and varying rainfall gauge densities, thereby forming a systematic and representative testing framework. Results demonstrate that, compared to the traditional method, the proposed approach maintains high detection rates for actual disasters while significantly reducing the false alarm rate. The new method completely eliminated the three false alarms generated by the traditional approach, demonstrating a substantial improvement in warning precision. Specifically, using single-station warnings for nearby stations ensures rapid response to local heavy rainfall, while multi-station and areal rainfall warnings for more distant stations effectively capture regional events and reduce false alarms caused by gauge failures or localized convective storms. By integrating the sensitivity of point rainfall information with the stability of regional rainfall patterns, the proposed method substantially enhances the reliability and robustness of flash flood warnings, providing strong technical support for timely evacuation and disaster risk reduction in mountainous flash flood prone regions.